Validation of RP-SPF framework: a systematic method for requirements reuse in software product lines - Badamasi, Imam Ya'au; Nordin, Azlin; Salleh, Norsaremah; , (Blue Eyes Intelligence Engineering and Sciences Publication, 2019)
Reuse of requirements is crucial activity in software development especially across software product line engineering (SPLE), which involves two main processes known as domain engineering and application engineering. With these two processes SPLE enables systematic reuse of requirements through proper planning and development. This paper presents methodology and result of survey of experts for validating a proposed systematic requirement reuse approach named requirements pattern for software product families (RP-SPF) framework. During the survey, 14 experts in requirements engineering (RE), SPLE and software development responded and gave their opinions on RP-SPF framework. The result of the survey shows that RP-SPF approach is suitable and can effectively improve requirements engineering activities of SPLE. © BEIESP.